The effects of fibroblast growth factor-2 delivered via a Gelfoam patch on the regeneration of myringosclerotic traumatic eardrum perforations lying close to the malleus - Jin, Zhong-hai; Dong, Yi-Han; Lou, Zi-Han (American journal of otolaryngology, 2017)
We evaluated the effects of fibroblast growth factor-2 (FGF-2) delivered via a Gelfoam patch on the regeneration of myringosclerotic traumatic tympanic membrane perforations (TMPs) lying close to the malleus. A prospective, randomized, controlled clinical study. A university-affiliated teaching hospital. We prospectively analyzed, in a randomized manner, the outcomes of treatment for traumatic TMPs constituting >25% of the tympanic membrane. The closure rates, closure times, and otorrhea rates were compared among patients treated via FGF-2-containing Gelfoam patches, Gelfoam patches alone, and observation only. We analyzed data from 138 patients. The perforation closure rates in the FGF-2 plus Gelfoam patch, Gelfoam patch, and observation alone groups were 97.9, 89.8, and 70.7%, respectively. Both the FGF-2 plus Gelfoam and Gelfoam alone groups exhibited significantly higher closure rates than the observational group (both p<0.05).The mean closure times were 15.7±5.1, 24.8±4.9, and 35.7±9.2days in the FGF-2 plus Gelfoam patch, Gelfoam patch alone, and observation alone groups, respectively. The FGF-2 plus Gelfoam patch group exhibited a significantly shorter closure time than the Gelfoam patch alone and observation alone groups (p<0.05). The incidences of purulent otorrhea were 14.6, 6.1, and 4.9% in the FGF-2 plus Gelfoam patch, Gelfoam patch alone, and observation alone groups, respectively. Surprisingly, 7 of 7 (100.0%) perforations associated with purulent otorrhea completely closed in the FGF-2 plus Gelfoam patch group; however, no such perforation healed in either the Gelfoam alone or observation alone group. FGF-2 plus Gelfoam patching significantly shortened the closure time compared to observation and Gelfoam patching alone, and it significantly improved the closure rate (compared to observation alone) of myringosclerotic perforations lying close the malleus. FGF-2 plus Gelfoam patching is a valuable, minimally invasive alternative treatment that may be readily applied to outpatient settings.